Effects of Smiley Face Scales on Visual Processing of Satisfaction Questions in Web Surveys. (December 2018) - Stange, Mathew; Barry, Amanda; Smyth, Jolene; Olson, Kristen
Web surveys permit researchers to use graphic or symbolic elements alongside the text of response options to help respondents process the categories. Smiley faces are one example used to communicate positive and negative domains. How respondents visually process these smiley faces, including whether they detract from the question's text, is understudied. We report the results of two eye-tracking experiments in which satisfaction questions were asked with and without smiley faces. Respondents to the questions with smiley faces spent less time reading the question stem and response option text than respondents to the questions without smiley faces, but the response distributions did not differ by version. We also find support that lower literacy respondents rely more on the smiley faces than higher literacy respondents.